Dinamika Transformasi Penyuluhan Kesehatan Digital Pada Masa Pandemi Covid-19 - Nurdin, Ambia (Teewan Journal Solutions, 2024)
This article discusses the dynamics of the transformation of digital health education during the COVID-19 pandemic. The pandemic has forced the healthcare system to adapt quickly, including in the provision of health information to the public. Health education, which was previously predominantly conducted conventionally, has now undergone significant transformation towards digital platforms. Through a qualitative research approach, we explore changes in health education strategies, community responses, and their impact on health decision-making. The research findings indicate that the digitization of health education provides broader accessibility but also presents new challenges related to access gaps and digital literacy. Additionally, this article describes how health educators and stakeholders have successfully addressed these challenges and enhanced the effectiveness of digital health education. By analyzing the dynamics of this transformation, the article provides valuable insights for policy development, further research, and the implementation of best practices in digital health education during the pandemic and beyond.